Phytotechnical behavior of ’Prata-Anã’ banana and progeny hybrids - Donato, Sérgio Luiz Rodrigues; Arantes, Alessandro de Magalhães; Silva, Sebastião de oliveira e; Cordeiro, Zilton José Maciel (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the phytotechnical behavior of ’Prata-Anã’ banana and four progeny hybrids, during two production cycles, in the Perímetro Irrigado do Estreito, southwest of Bahia state, Brazil. The experimental design was completely randomized with five treatments: cultivar ’Prata-Anã’ and the hybrids Fhia-01 (BRS Fhia Maravilha), BRS Fhia-18, Fhia 18 and PA42-44, with ten replicates. Phenotypic vegetative descriptors, cycle length and yield were measured. Increases occurred between cycles for: plant height, pseudostem perimeter, number of hands and fruits, and yield. The Fhia-18 hybrid showed greater size and pseudostem perimeter, and ’Prata-Anã’ had the smallest, (with maintenance of this character in the PA42-44). The hybrids were similar in the number of suckers produced. BRS Fhia-18, PA42-44 and Fhia-1 were early for harvest and had greater fruit length than ’Prata-Anã’. Fhia-18 produced more fruit and PA42-44 had fewer hands compared to the parental cultivar. BRS Fhia-18, Fhia-18 and Fhia-1 are more productive than the parental cultivar. ’Prata-Anã’ is more susceptible to yellow sigatoka, while PA42-44 is resistant, with greater retention of leaves at harvest; however, both have similar yields.